Introduction of Solar Desalination Technology with Cooling Fans for Clean Water Supply in Warmon Kokoda Village Sorong City Southwest Papua - Kristin Seru Matonda; Siti Ani Umkabu; Supriyatna Supriyatna; Yufita Fenetiruma; Yakomina Ronetha Burdam; Salsabila Suega; Fajar Efendi; Febrian Andi Hidayat; Jaharudin Jaharudin; Budi Santoso; Lisa Dewi Ramadany (Samakta: Jurnal Pengabdian Kepada Masyarakat, 2026)
The issue of clean water availability in coastal areas remains a serious challenge, particularly due to increasing seawater intrusion, which causes groundwater to become brackish and unfit for consumption. This condition is also experienced by the community in Warmon Kokoda Village, Sorong Regency, who have long depended on well water sources with high salinity levels. This community service activity aimed to introduce and train residents in the use of single-roof solar desalination technology with a solar-powered cooling fan as an energy-efficient and environmentally friendly solution for brackish water purification. The approach used was Participatory Action Research (PAR), in which the community was actively involved in socialization, learning, and hands-on practice in the manufacture and operation of the device. The results of this activity showed an increase in community knowledge about the working principles and benefits of solar desalination technology, as evidenced by the community's ability to conduct trials on the device. Technical tests showed that the device was able to reduce the salinity of brackish water from 5% to 0%, producing water suitable for consumption according to WHO standards, with good thermal efficiency for the household category. This activity had a significant impact in providing access to safe and potable water for the local community, as well as increasing independence in water resource management.